Lens-Induced Uveitis Triggered by Intravitreal Injection 40 Years after Primary Congenital Cataract Surgery with Aphakia - Sophia El Hamichi; Rafael J. Aguilar; Veronica Kon Graversen; Aaron S. Gold; Audina M. Berrocal; Timothy G. Murray (Case Reports in Ophthalmology, 2020)
We report a case of a 42-year-old male with a history of bilateral congenital cataract surgery performed at 2 years of age. The patient was left with aphakia, secondary glaucoma, and a history of diabetic macular edema in the setting of diabetes mellitus type 1. The right eye became prephthisical from his congenital surgical repair, and his left eye presented with an acute pseudo-endophthalmitis developing after the seventh intravitreal injection to treat the macular edema. The eye then presented with decrease in vision, periocular injection, and a diffuse inflammatory reaction focused around the anterior residual lens capsule. The patient underwent surgical removal of the residual capsule and primary vitrectomy repair of the eye, achieving a significant improvement in visual symptoms and recovery of visual and anatomic function.